Nexus Between Accounting Ethics and Sustainability Practices in Nigeria - Sehilat Abike Bolarinwa; Khadijat Adeola Idowu; Abass Bello (Sinergi International Journal of Accounting and Taxation, 2026)
As Nigeria joins the rest of the world to adopt IFRS-S1 and IFRS-S2 reporting, there are public concerns about sustainability report despite accounting ethical principles in place. This study examines the relation between accounting ethics and sustainability practices in Nigeria. Adaptive questionnaire is used to source for data. Multi-regression method is used to analyse the data while survey research design was employed. The sample size of the study is 384 Nigerian accountants which are selected through stratified sampling technique. This study uses convergent validity and Cronbach's alpha reliability test for the data. The findings reveal that accounting ethics show partial and dimension-specific influence, with stronger effects in environmental and social dimensions and very limited explanatory power in governance, though effects vary across dimensions. Integrity, professional competence and due care, confidentiality, and professional behaviour significantly enhance environmental sustainability practices. For social sustainability, integrity, professional competence, and professional behaviour exert positive effects, while confidentiality shows a negative but significant influence. In terms of governance sustainability, integrity emerges as the only consistent and significant predictor. Overall, integrity is the most influential ethical principle across ESG dimensions. The study concludes that accounting ethics play a critical but context-dependent role in promoting sustainability practices in Nigeria. It recommends as firms should strengthen integrity, professional competence and due care with professional behaviour as the trio are moderately consistent and support sustainability practices to adopt ESG practices for improved transparency and accountability.